Pengaruh Modal Intelektual Terhadap Kinerja Keuangan Dan Kinerja Pasar (Studi Empiris Pada Perusahaan Yang Terdaftar di Indeks LQ-45 Tahun 2012-2014) - Hardina, Lulu; , Dr. Fatchan Achyani, SE, M.Si (2016)
The research aims to analyze the influence of Capital Employed Efficiency (CEE), Human Capital Efficiency (HCE) and Structural Capital Efficency (SCE) toward financial performance (ROA and Growth Revenue) and market performance (MtBV) at company which listing in Indek LQ-45 from 2012-22014. This research uses 23 company sample which listing company in indeks LQ-45. Analysis of data in this research using double linear regresion analysis to verify and to prove the research hypothesis. Analysis result CEE have a significant influence toward ROA and MtBV, HCE only have a significant influence toward Revenue Growth and SCE only have a significant influence toward MtBV.